The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1177/0305735607068885
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to music and cognitive performance: tests of children and adults

Abstract: This article reports on two experiments of exposure to music and cognitive performance. In Experiment 1, Canadian undergraduates performed better on an IQ subtest (Symbol Search) after listening to an up-tempo piece of music composed by Mozart in comparison to a slow piece by Albinoni. The effect was evident, however, only when the two pieces also induced reliable differences in arousal and mood. In Experiment 2, Japanese 5-year-olds drew for longer periods of time after singing or hearing familiar children's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(186 citation statements)
references
References 49 publications
5
159
0
12
Order By: Relevance
“…This hypothesis is perhaps best illustrated by the Mozart effect (Raucher, Shaw & Ky, 1994;Schellenberg, Nakata, Hunter & Tamoto, 2007). These authors concluded that different types of music can improve performance on cognitive tests and the effect mediated by a change in the emotional state of the listener.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is perhaps best illustrated by the Mozart effect (Raucher, Shaw & Ky, 1994;Schellenberg, Nakata, Hunter & Tamoto, 2007). These authors concluded that different types of music can improve performance on cognitive tests and the effect mediated by a change in the emotional state of the listener.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Ivanov and Geake (2003), upper-primary school-aged children exposed to musical pieces by Mozart or Bach in a school setting outperformed children in a control class on a Paper Folding Task. Furthermore, children remained engaged for longer in a drawing task when exposed to cheerful, familiar, age-appropriate music rather than classical music including Albinoni's Adagio in G-minor for Strings and Organ (Schellenberg et al, 2007). However, other studies failed to find cognitive benefits resulting from music exposure.…”
Section: Methodsmentioning
confidence: 99%
“…see Isen, 2008). A series of studies conducted by Schellenberg and collaborators supported the arousal and mood hypothesis (Husain, Thompson, & Schellenberg, 2002;Schellenberg, Nakata, Hunter, & Tamoto, 2007;Thompson, Schellenberg, & Husain, 2001; for a review, see Schellenberg, 2012).…”
mentioning
confidence: 98%
“…For instance, Boone and Cunningham's procedure involved a phase of significant modelling by the experimenter, which may be considered a confounding factor when analysing the children's responses. Mote (2011) andSchellenberg, Nakata, Hunter, andTamoto (2007) found superior performance in preschool children's ability to recognise emotion when using music derived from culturally familiar children's songs rather than classical or adultdirected music, thus highlighting an important influence of materials.…”
Section: Type Of Task Materials and Type Of Responses (Explicit Vs mentioning
confidence: 99%